1983
DOI: 10.1007/bf00037768
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in mediterranean-type shrublands near Eneabba, south-western Australia

Abstract: Kwongan vegetation (sclerophyllous shrublands) growing on a single soil type was surveyed over a 5 000 km 2 area centered about Eneabba, Western Australia. All samples were on laterite, a deeply weathered, infertile soil developed since the Tertiary over much of the ancient, subdued landscape of south-western Australia. The vegetation was rich in angiosperm plant species and, although quite uniform in structure, highly variable floristically, suggesting the existence of a complex mosaic of species distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…Burgman and Newbey (1989) collected extensively from the study area and found 15% of the State's named flora. About 20% of the taxa they collected were undescribed or of uncertain status, and 10% were considered rare, geographically restricted or very poorly known; findings consistent with other areas of Western Australia with similar landforms and vegetation types (Newbey 1979;Monk et al 1979;Griffin et al 1983;Hopkins et al 1983).…”
Section: Introductionsupporting
confidence: 58%
“…Burgman and Newbey (1989) collected extensively from the study area and found 15% of the State's named flora. About 20% of the taxa they collected were undescribed or of uncertain status, and 10% were considered rare, geographically restricted or very poorly known; findings consistent with other areas of Western Australia with similar landforms and vegetation types (Newbey 1979;Monk et al 1979;Griffin et al 1983;Hopkins et al 1983).…”
Section: Introductionsupporting
confidence: 58%
“…1987;Brown et at. 1988) are inadequate to assess species turnover, it would appear from casual observation to be considerably less than that recorded from kwongan (Griffin et at. 1983;Hopkins & Griffin 1984),…”
Section: Discussionmentioning
confidence: 83%
“…1979;Rice & Westoby 1983a, b;Lamont et al 1984), At scales of up to 0,1 ha, kwongan (sclerophyllous shrubland in southwestern Australia) is one ofthe most diverse communities in the temperate world (Lamont et al 1984), with up to 103 vascular species in 0,1 ha (Brown & Hopkins 1 983), a high species turnover (Griffin et al 1983;Hopkins & Griffin 1984), and considerable endemism (Lamont et al 1984), By contrast, woodlands with herbaceous understoreys are generally thought to be relatively poor in species; Whittaker et al (1979) recorded a mean of only 53 species in 0,1 ha in mallee.…”
Section: Introductionmentioning
confidence: 96%
“…The prominence of the Proteaceae and Myrtaceae in the Stirling Range is a well documented feature of kwongan vegetation (George et al 1979;Griffin et al 1983;Hopkins & Griffin 1984;Lamont et al 1984;Froend 1987;Wills 1989). The Proteaceae are the most abundant group in the Stirling Range and provide a substantial food-base for the fungus.…”
Section: Impact Of P Cinnamomi On Floristic Structurementioning
confidence: 96%
“…The disease causes not only the decline in species richness of susceptible species at a site, but also a change in plant community structure and biomass as field resistant species, especially herbaceous perennials, become more abundant. The prominence of the Proteaceae and Myrtaceae in the Stirling Range is a well documented feature of kwongan vegetation (George et al 1979;Griffin et al 1983;Hopkins & Griffin 1984;Lamont et al 1984;Froend 1987;Wills 1989). The Proteaceae are the most abundant group in the Stirling Range and provide a substantial food-base for the fungus.…”
Section: Impact Of P Cinnamomi On Floristic Structurementioning
confidence: 99%